2019
DOI: 10.1101/562447
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the Human Segmentation Clock with Pluripotent Stem Cells

Abstract: 32 33 Keywords: segmentation clock, somitogenesis, human mesoderm development, induced 34 pluripotent stem cells, step-wise in vitro mesoderm differentiation, disease modeling 35 Pluripotent stem cells (PSCs) have increasingly been used to model different aspects 36 of embryogenesis and organ formation 1 . Despite recent advances in the in vitro 37 induction of major mesodermal lineages and mesoderm-derived cell types 2,3 , 38 experimental model systems that can recapitulate more complex biological features 39… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…Treatment of mouse iPSM with 2DG decelerated the segmentation clock in a dose-dependent manner as described previously 34 (Fig. 3a,b): the oscillation period of mouse iPSM treated with 10 mM 2DG was 191 ± 1 min (mean ± SD), which was between the untreated mouse iPSM period (147 ± 4 min) and the reported human iPSM period (322 min) 6 .…”
Section: Inhibiting Glycolytic Activity Decelerates the Segmentation ...supporting
confidence: 64%
See 1 more Smart Citation
“…Treatment of mouse iPSM with 2DG decelerated the segmentation clock in a dose-dependent manner as described previously 34 (Fig. 3a,b): the oscillation period of mouse iPSM treated with 10 mM 2DG was 191 ± 1 min (mean ± SD), which was between the untreated mouse iPSM period (147 ± 4 min) and the reported human iPSM period (322 min) 6 .…”
Section: Inhibiting Glycolytic Activity Decelerates the Segmentation ...supporting
confidence: 64%
“…We next investigated the effect of metabolism on the protein stability profile. While both glycolytic activity and electron transport chain activity are involved in the segmentation clock and somitogenesis 12,18,[20][21][22][23][24] , we have recently found that a glycolysis inhibitor, 2-Deoxy-D-glucose (2DG), and an electron transport chain inhibitor, sodium azide, decelerate the segmentation clock through different mechanisms: 2DG decelerates HES7 protein degradation whereas sodium azide elongates HES7 intron processing delay 34 .…”
Section: Inhibiting Glycolytic Activity Decelerates the Segmentation ...mentioning
confidence: 99%
“…1a), as other groups have recently reported 712 . In essence, our PSM induction protocol is based on activation of WNT and FGF signaling as well as inhibition of TGFβ and BMP signaling 9,12 . Prior to the PSM induction, mouse ESCs, which are in the naïve pluripotent state, were pretreated with ACTIVIN A and bFGF and converted to mouse epiblast-like cells (EpiLCs) that possess primed pluripotency as human iPSCs do.…”
Section: Mainmentioning
confidence: 59%
“…Then the cells were cultured in CDMi containing SB431542 (10 μM), DMH1 (2 μM), CHIR99021 (10 μM), and bFGF (20 ng/ml) for another 3.5 days to induce human PSM cells. For the degradation assay, our 2 step induction protocol 12 was used. Human iPSCs were seeded on a 35 mm dish coated with iMatrix-511 silk and cultured for 5 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation